New horizons for Malaysia's landscape education: gate project across cultures and continents - Hussein, Mohd Kher; Kabai, Robert (Elsevier, 2015)
GATE is an Erasmus Mundus mobility project funded by the European Commission (2012-2016). This programme has opened up an opportunity to the Asian university students/staff to further study in European countries and to enhanced university partnerships. GATE is quite new, thus landscape students/staff need to grasp this opportunity for their better future prospect. This paper highlights the GATE project possibility in enriching the environment for landscape study and contributing to the academic excellence of Malaysia's landscape education. GATE project acts as a new horizon in landscape education, enhances the skills, qualifications and benefits linguistically and culturally the respective universities.